The Effect of King Grass Silage on the Nitrogen Balance and Hematological Profile of Ettawa Grade Male Goat - S. Sunarso (International Journal of Science and Engineering, 2012)
The aims of this research was to study the nutritional value of ensiled King Grass (Pennisetum purpuphoides) to be applied for goat. Twelve Ettawa grade male (PE), + 10 months old, and with average body weight of 19.45 + 3.03 kg were used to determine the voluntary intake, balance nitrogen and their hematological profile. All of the animals were randomly allotted at individual pens. Data were analyzed statistically using analysis of variance, based on completely randomized design arrangement with four treatments (level of King Grass silage) and three replicates. Treatment means were compared using Duncan multiple range test. The result showed that increasing level of King Grass silage within ration significantly increased the average dry matter (DM) intake per metabolic body weight. In fact, the daily DM intake, nitrogen balance, blood hemoglobin and blood hematocrit of the experimental animals were not affected by level of King Grass silage feed. Experiment had no bad effect on healthy condition of the treated goat, so it implies that conserving grass as silage and then feeding grass silage to goat might be implemented by farmers to secure the continuous supply of green forage to keep the goat production sustainability all year round. [Keywords: silage, nitrogen balance, haemoglobin, haematocryt, goat]